The failure factors of implementing tqm at construction organization at Kuantan - Mohd Nordin, Zainol (2016)
Total quality management (TQM) is a systematic and comprehensive approach in organizational management. The aim of TQM is to improve the current quality of products and services in organization production. Successful implementing TQM can improve a company profitability and also can achieve customer satisfaction. TQM always famous at manufacturing industries and not more familiar in construction organization. Implemented TQM in construction organizations are not necessarily successful on the whole activities. This may be caused by poor management in the implementation of these activities. This research was identified the factors that contribute to failure. For this study quantitative research has been use to collect the data. There are 77 respondents from Construction organization G6 and G7 are involve in this research. This research aim to identify the failure factor and effect the organization performance. SPSS as a tool that use to analyse the data from respondents answered. From the result, Poor management in communication is a main failure factor in implementing TQM. Besides that, all the failure factors was effected the construction organization performance in term of scope, cost and time.